1991
DOI: 10.1159/000156537
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Activity during Vocalization in the Squirrel Monkey

Abstract: Inorder to find out which muscles are involved in the respiratory component of primate phonation, the activity of 17 abdominal and thoracic muscles was recorded during vocalization in the squirrel monkey. Vocalization-correlated activity was found in the musculi obliquus externus et internus, rectus et transversus abdominis, intercostalis externus et internus and intercartilagineus. It was lacking in the mm. iliocostalis, latissimus dorsi, longissimus dorsi, rhomboideus, serratus posterior superior, trapezius,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…21,24,38,61,64,67,68,70 -75 Different individuals seem to develop somewhat different patterns of muscle recruitment to effect the same results in terms of air pressure, which complicates the picture. 24,55,61,71,74 Relatively little is known about muscular recruitment for breathing control during the vocalizations of nonhuman primates, but evidence mostly from electrically stimulated calls in squirrel monkeys 76 and two macaque species 77 indicates this may be very different from the patterns in humans, involving the diaphragm and abdominal muscles, with only a limited role for the intercostals.…”
Section: How Is Subglottal Air Pressure Controlled?mentioning
confidence: 99%
“…21,24,38,61,64,67,68,70 -75 Different individuals seem to develop somewhat different patterns of muscle recruitment to effect the same results in terms of air pressure, which complicates the picture. 24,55,61,71,74 Relatively little is known about muscular recruitment for breathing control during the vocalizations of nonhuman primates, but evidence mostly from electrically stimulated calls in squirrel monkeys 76 and two macaque species 77 indicates this may be very different from the patterns in humans, involving the diaphragm and abdominal muscles, with only a limited role for the intercostals.…”
Section: How Is Subglottal Air Pressure Controlled?mentioning
confidence: 99%
“…There are few detailed studies of breath control during vocalizations in nonhuman primates, apart from the extensive series of laboratory studies on respiratory muscle activity and the neural control of vocalizations in Saimiri sciureus (Jurgens, 1982(Jurgens, , 1988Kirzinger, 1982, 1984;Jurgens and Richter, 1986;Sutton and Jurgens, 1988;Jurgens and Schreiver, 1991;Kirzinger and Jurgens, 1994) and the studies on macaques (Macaca nemestrina and M. fascicularis) (West and Larson, 1993;Larson et al, 1994). These workers reported that vocalizations occurred only on exhalations and primarily involved abdominal muscles rather than intercostal muscles, which were active prior to vocalizations in the study of macaques by West and Larson (1993) and not consistently active during vocalizations in the studies of either genus.…”
Section: Evidence Of Differences In the Muscular Control Of Breathingmentioning
confidence: 99%
“…These workers reported that vocalizations occurred only on exhalations and primarily involved abdominal muscles rather than intercostal muscles, which were active prior to vocalizations in the study of macaques by West and Larson (1993) and not consistently active during vocalizations in the studies of either genus. Jurgens and Schreiver (1991) speculated that the intercostal muscles in S. sciureus could be involved in supporting the thorax and providing anchorage against which the abdominal muscles could act, rather than producing respiratory drive. West and Lar-son (1993) suggested that in macaques the diaphragm could have a central role during vocalizations similar to that of the intercostals in humans.…”
Section: Evidence Of Differences In the Muscular Control Of Breathing For Human Speech And Nonhuman Primate Vocalizationsmentioning
confidence: 99%